Impact of link-removal on the air transportation network. - Lee, Chun Hoe. (2012)
As one of the critical infrastructure network, the air transportation network provides the fastest way for millions of people to travel around the world every day. At the same time, it is also responsible for the world-wide propagation of infectious diseases such as the influenza